2016
DOI: 10.1021/acs.jpca.6b03487
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on F + NH2Cl Reaction: Nucleophilic Substitution at Neutral Nitrogen

Abstract: The SN2 reactions at N center, denoted as SN2@N, has been recognized to play a significant role in carcinogenesis, although they are less studied and less understood. The potential energy profile for the model reaction of SN2@N, chloramine (NH2Cl) with fluorine anion (F(-)), has been characterized by extensive electronic structure calculations. The back-side SN2 channel dominates the reaction with the front-side SN2 channel becoming feasible at higher energies. The minimum energy pathway shows a resemblance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 52 publications
(95 reference statements)
3
31
0
Order By: Relevance
“…New geometries, carefully selected and added to improve the PES, are generated in quasi-classical trajectory (QCT) simulations and by the Holebuster subprogram. 40 ROBOSURFER iterations are performed at the following collision energies (kcal mol À1 ) used in the dynamics computations with the maximal values of the b impact parameter (the distance between the velocity vectors of the reactants in bohr) in parentheses: 64, 27,13,11,13,27,17,62,36 Quasi-classical trajectory simulations are performed at seven collision energies: 0.9, 6.9, 10.0, 20.0, 30.0, 40.0, and 46.1 kcal mol À1 to investigate the dynamics of the F À + NH 2 Cl reaction. The spatial orientation of the reactants is randomly sampled, and the initial distance between the F À ion and the center of mass of the NH 2 Cl molecule is set to ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi x 2 þ b 2 p bohr, where x ¼ 30.0 bohr and the b impact parameter is varied between 0 and b max , the distance where the reaction probability becomes zero, with a step size of 1.0 bohr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…New geometries, carefully selected and added to improve the PES, are generated in quasi-classical trajectory (QCT) simulations and by the Holebuster subprogram. 40 ROBOSURFER iterations are performed at the following collision energies (kcal mol À1 ) used in the dynamics computations with the maximal values of the b impact parameter (the distance between the velocity vectors of the reactants in bohr) in parentheses: 64, 27,13,11,13,27,17,62,36 Quasi-classical trajectory simulations are performed at seven collision energies: 0.9, 6.9, 10.0, 20.0, 30.0, 40.0, and 46.1 kcal mol À1 to investigate the dynamics of the F À + NH 2 Cl reaction. The spatial orientation of the reactants is randomly sampled, and the initial distance between the F À ion and the center of mass of the NH 2 Cl molecule is set to ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi x 2 þ b 2 p bohr, where x ¼ 30.0 bohr and the b impact parameter is varied between 0 and b max , the distance where the reaction probability becomes zero, with a step size of 1.0 bohr.…”
Section: Methodsmentioning
confidence: 99%
“…20 Theoretical investigations of the S N 2 reactions at N center began with the characterization of the potential energy surfaces (PESs) of X À + NH 2 Y and N(CH 3 ) 2 Y [X, Y ¼ F, Cl, Br, I] using lower-level ab initio [21][22][23][24] and density functional theory (DFT) methods. [25][26][27] Later, Bickelhaupt and co-workers studied the impact of replacing the central carbon atom in S N 2 reactions with several other atoms by performing an activation strain analysis. 28,29 In 2018 one of the present authors reported benchmark classical and adiabatic CCSD(T)-F12b/complete-basis-set-quality stationary-point energies and geometries taking also into account the correlation of core electrons both for identity and non-identity X À + NH 2 Y [X, Y ¼ F, Cl, Br, I] reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic reaction coordinate (IRC) 44 calculation was performed to confirm that every transition state connects with the corresponding reactant and product through the minimized-energy pathway. Previous results 25,27 reported that basis set effects on the energy barriers of the S N 2@N reactions are small. As CCSD(T) energies for F − + NH 2 Cl stationary points reported by Zhang et al, 27 regarding the augcc-pVXZ (X = D, T, Q, and 5) basis sets enlarged from X = D to 5, the CCSD(T) reference data are converged fast for the minima with the deviations within 2 kcal/mol, whereas those for the transition states are converged slightly slower with the deviations around 2−5 kcal/mol.…”
Section: Methodsmentioning
confidence: 95%
“…Recently, Wang et al 26 employed a multilevel quantum mechanics and molecular mechanics approach to study the reaction HO − + NH 2 Cl in aqueous solution, and also found that S N 2@N reaction is a faster reaction than the corresponding S N 2@C reaction. Zhang and Yang et al 27 explored the potential energy profile for the model S N 2 reaction of F − with NH 2 Cl by extensive electronic structure calculations and found that the backside channel dominates the reaction, and the proton transfer pathway is more competitive for S N 2@N reaction compared with the corresponding S N 2@C reaction. Very recently, they 28 also studied the atomistic dynamics of the above reaction by using direct dynamics simulations and found strikingly distinct features from those determined for a S N 2@C congener F − + CH 3 Cl.…”
Section: Introductionmentioning
confidence: 99%
“…However, the above studies are mostly done for the S N 2 reaction at the carbon center; nitrogen-centered S N 2 reactions have been less studied. For the title reaction, F – + NH 2 Cl , in gas phase, Buhl and Schaefer performed ab initio DZP/SCF calculations and obtained the barrier height of the Walden-inversion pathway at −6.9 kcal/mol. Liu et al studied the reaction profiles of this reaction for the indirect hydrogen-bond complex, proton transfer, and front side mechanism with the coupled-cluster singles and doubles with perturbative triples (CCSD­(T))/CBS theory.…”
Section: Introductionmentioning
confidence: 99%